KOMPONEN KIMIA DAN POTENSI PENGGUNAAN LIMA JENIS KAYU KURANG DIKENAL ASAL JAWA BARAT - Novitri Hastuti; Lisna Efiyanti; Gustan Pari; Saepuloh; Dadang Setiawan (Jurnal Penelitian Hasil Hutan, 2017)
There are about 4,000 timber producing trees grow naturally in Indonesia, which comprise of commercially and lesser known wood species. Wood chemical component analysis is one indicator for timber utilization. This paper studies the chemical components of five lesser-known wood species originated from West Java namely ki bugang (Arthophyllum diversifolium Bl.), sempur lilin (Dillenia obovata Hoogl.), cangcaratan (Lithocarpus sundaicus Bl.), ki pasang (Prunus javanica Miq ), and ki langir (Othophora spectabilis Bl). The analysis was conducted according to the testing standard of Norman Jenkin, Indonesian National Standard (SNI) and TAPPI. Results show that Ki bugang has the highest content of both of cellulose and pentosan about 52.57% and 21,37%, respectively. Cangcaratan wood has the highest lignin content about 31.84 %. Ki langir has the highest solubility in cold water, alcohol benzene and NaOH about 3.34%, 2.75%, and 22.17%, respectively. In addition, sempur lilin has the highest solubility in hot water about 8.56%. The highest ash content is 3.60% belongs to Ki langir and the highest silica content is 1.92% belongs to sempur lilin. Based on the chemical content, cangcaratan wood is recomended for pulp and energy purposes and ki bugang wood is recommended for bio-ethanol.